Behavioural adaptation of skiers to climatic variability and change in Ontario, Canada. (October 2015) - Rutty, Michelle; Scott, Daniel; Johnson, Peter; Jover, Eric; Pons, Marc; Steiger, Robert
Abstract: Increasing research highlights the vulnerability of the alpine ski sector to climatic variability and change. The literature has focused predominantly on supply-side vulnerability, with limited insight into tourists' behavioural response to marginal snow conditions and ski resort closures. Using an in-situ survey ( n =2448), this study examines how skiers in Ontario (Canada) would change their participation patterns if their preferred ski resort were closed due to a lack of snow. The survey focuses on current behavioural responses, rather than decisions based on future scenarios of climate change. Results show that substitution behaviours (i.e., spatial, temporal, activity) differ pending whether the resort is closed for the day, closed until mid-season or closed permanently, with differences ( p <0.05) recorded based on skier market segments. The results also indicate that beginner and infrequent skiers, as well as parents with children enroled in ski lessons, are more likely to either ski less and/or stop skiing altogether, while experienced and core skiers are more likely to engage in spatial substitution. Season pass holders and those at large resorts were also more likely to engage in spatial substitution. Managerial implications as a result of a likely shift in ski demand patterns in Ontario are discussed, with future research needs identified to appraise the differential community-level consequences and future climate adaptation strategies of ski tourism. Management implications: The behavioural response of skiers to changing climatic conditions will be a decisive factor in the vulnerability and sustainability of ski tourism. Fundamental to assessing the contemporary climate risk of the multi-billion dollar ski industry, as well as to estimate how future climate change could alter demand patterns in regional ski tourism marketplaces, is to understand skiers' behavioural adaptation to inter-annual climate variability. As skiers engage in behavioural substitution (temporal, spatial, activity), a shift in ski demand patterns is likely. Skiers will concentrate at resorts that remain climatically operable, which will have important management implications with respect to individual resort capacity, visitor experience (e.g., crowding), and consequent impacts on surrounding ski area businesses and communities. Climatically advantaged ski areas and communities will need to prepare for development pressures, including investments in ski terrain expansion and infrastructure to increase snowmaking capacity (including water access and storage), as well as ease increased crowding on trails, in parking lots, inside chalets and lift lines. The results from this study offer decision support to ski resort operators and local tourism officials concerned about how their visitors will respond to changing climatic conditions and the implications for local economic development and real-estate.